2013
DOI: 10.1002/path.4165
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐II is produced by, signals to and is an important survival factor for the mature podocyte in man and mouse

Abstract: Podocytes are crucial for preventing the passage of albumin into the urine and, when lost, are associated with the development of albuminuria, renal failure and cardiovascular disease. Podocytes have limited capacity to regenerate, therefore pro-survival mechanisms are critically important. Insulin-like growth factor-II (IGF-II) is a potent survival and growth factor; however, its major function is thought to be in prenatal development, when circulating levels are high. IGF-II has only previously been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
0
22
1
Order By: Relevance
“…Previously, we (13,33) showed that insulin predominantly signals through the IR and that IGFs signal predominately through the IGF-IR in the podocyte. Therefore, we genetically induced insulin and IGF resistance in podocytes by knocking down the major receptors through which insulin and IGFs signal, the IR and IGF-IR.…”
Section: Rendering the Podocyte Insulin Resistant Reduces Vegf-a Prodmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we (13,33) showed that insulin predominantly signals through the IR and that IGFs signal predominately through the IGF-IR in the podocyte. Therefore, we genetically induced insulin and IGF resistance in podocytes by knocking down the major receptors through which insulin and IGFs signal, the IR and IGF-IR.…”
Section: Rendering the Podocyte Insulin Resistant Reduces Vegf-a Prodmentioning
confidence: 99%
“…Short hairpin (sh)RNA knockdown of the IR and IGF-IR was performed as previously reported (13,33). We studied two clones with similar levels of receptor knockdown in this report: 75% knockdown for the IR and 81% knockdown for the IGF-IR.…”
Section: Measurement Of Secreted Vegf-a Proteinmentioning
confidence: 99%
See 3 more Smart Citations